PENERAPAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN MATEMATIS SISWA KELAS VII2 SMP NEGERI 5 PEKANBARU - Suhardi, Andini Leona; Yuanita, Putri; Suhermi, Suhermi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research to improve the learning process and the student’s mathematical understanding skill by Discovery Learning model. The type of this research is Classrom Action Research with two cycles. The subject of this research were students of class VII2 SMPN 5 Pekanbaru. This study was conducted in the second semester of academic year 2017/2018. The research instruments used are mathematical learning instruments (Syllabus, Lesson Plans, and Student Worksheet) and instruments for collecting data (Observation Sheets and Mathematical-Understanding Tests). The observation sheets were used to find out the data of students and teacher activity during learning process wich would analyzed quantitatively and qualitatively, and mathematical understanding test were used to collect the student’s mathematical understanding skill outcomes which would analyzed quantitatively. Based on the analysis of the observation sheets showed that implementation of learning process on cycle II had happened improvement from implementation on cycle I. Result of the test indicated that the student’s learning achievement for the first is 50,9 improved in cycle I to 75,68 and improved to 85,30 in cycle II. The improvement of student’s learning achievement founded for each indicator of mathematical understanding skill: redefine the concept, appyling the concept logically, and associating various concepts in mathematics. Based on the result above, it can be concluded that the implementation of Discovery Learning model approach can improve the learning process and the students’ mathematical understanding skill outcomes at class VII2 SMP Negeri 5 Pekanbaru.Key Words: Discovery Learning, mathematical understanding skill, learning process